HEAT SOURCE DENSITY IN NON-LINEAR HEAT DISSIPATION PROCESSES (Proceedings of Scientific Conference on Multidisciplinary Studies, 2023)
This article is devoted to the study of the effect of heat source on ambient density in non-linear heat dissipation processes in multidimensional areas. In order to solve the linear heat dissipation equation in the process of work, an self-similar solution was built in accordance with the characteristics of the ambient density and heat source, reaction-diffusion processes were observed, theorems were proved. The following results were obtained from this work: front-end evaluation for the two-time linear heat dissipation equation, localization process was observed, finite velocity was calculated as approximate, new effects were observed, algorithm was built according to the obtained self-similar solution, program code was created in the programming language and the process was modeled. All results were compared.